Impact of Cost Structure on Indonesia Food Industry Value Added - Robiani, Bernadette; Mukhlis, Mukhlis; Hamira, Hamira; Apriani, Deassy (Faculty of Economics, Universitas Sriwijaya, 2024)
The food industry is a consistently growing sector, even in challenging economic conditions, driven by population growth and increased demand. Recognizing its importance, the Indonesian government has identified the food and beverage industry as a key sector in its Industry 4.0 roadmap. However, challenges such as reliance on imported raw materials and high labor absorption rates persist. This study analyzes the impact of cost structure on the value-added in Indonesia's food industry from 2017 to 2021, using data from Indonesia Statistics on large and medium industries. The Panel Data Regression results reveal that raw material costs and fixed capital costs positively and significantly affect value-added. These findings suggest that effective cost management, innovation, and the use of advanced technology are crucial for optimizing value-added in this sector.